Seeing Feelingly: A Phenomenological Inquiry Into the Mind/Body Experiences of Six Drama Students. Issue 5 (December 2013) - Nigh, Kelli
Abstract: What happened when six former drama students recalled their mind‐body experiences in a drama class that they attended together, throughout their childhood and adolescence? This article draws from a phenomenological research inquiry that examined these drama students' recollections of various unique warm‐up exercises. The warm‐up was originally introduced to gentle, calm and focus the students before rehearsals, but the students' perceptions began to change in unexpected ways. They simply seemed to see and feel differently, sometimes even extraordinarily. The aim of this article is to delve into these students' experiences in direct relation to a phenomenon referred to by Vivian Darroch‐Lozowski (2006) as "seeing feelingly." Calling for a clearer understanding and pedagogical application of feeling in the classroom, I frame this ontological mode of being within an interdisciplinary developmental perspective. To animate the gentling exercises in the imagination of the reader, the discussion intermittently assumes a dramatic, poetic style of writing. I claim that these students experienced numerous benefits from the exercises, for example, calmness, focus, an active imagination, an awareness of different modes of consciousness (thought, imagination, feeling) and a lived understanding of mind‐body inquiry. The concluding discussion attempts to move beyond the research claims, to assert through the text of a brief play, the existential and ontological significance of seeing feelingly.